Determination of trace nickel in chamomile tea and coffee samples by slotted quartz tube-flame atomic absorption spectrometry after preconcentration with dispersive liquid-liquid microextraction method using a Schiff base ligand - Saylan, Meltem; Zaman, Buse Tugba; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
In the present study, an accurate and selective preconcentration/extraction method was developed for the determination of nickel at trace levels. Slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS) combined with dispersive liquid-liquid microextraction (DLLME) was used to obtain a very low detection limit for nickel. A Schiff base ligand derived from the reaction of 5-bromosalicylaldehyde and o-phenylenediamine was used for the formation of a coordinate nickel complex. Under the determined experimental conditions, the detection and quantification limits of the DLLME-SQT-FAAS system were calculated as 4.9 and 16.4 ng/mL, respectively. Satisfactory analytical performance values of the SQT-FAAS, DLMME-FAAS and DLLME-SQT-FAAS methods were obtained and 1.8, 32.0, 66.4-fold enhancements in detection power were respectively obtained over the conventional FAAS system. The percent recovery ranges obtained for two different spike concentrations were 88.1-113.2% and 102.1-120.2% for coffee and chamomile tea samples, respectively.
Keywords: Chamomile tea; Coffee; DLLME; FAAS; Food composition; Food analysis; Nickel; Schiff base; SQT; METAL-IONS; WATER; ADSORPTION; SPECIATION; EXPOSURE; ELEMENTS; VANADIUM; Chemistry; Food Science & Technology